Individual analysis the competitive activity indicators of elite swimmer in a distance of 200 m. breaststroke - Skyriene V.V (Kharkov National Pedagogical University, 2010)
The analysis of features of competition activity is presented one of the best sportsmen. Basic dignities of competition activity of sportsman there is ability to develop high-rate of swimming of the starting cutting-off, distance and finish cutting-off. The low rate of motions is thus marked at a very long stroke. To failings it is possible to take the enough long stay of sportsman on a starting stand, considerable falling of speed of implementation of turns on motion distance. It is well-proven that a systematic and permanent analysis of competition activity is the important mean of training process control. Information about activity of sportsman on competitions at certain terms can be foundation for raising of purpose and tasks of preparation, choice of facilities and methods of their realization.